Growth of Malassezia furfur in Media with The Addition of Basil (Ocimum basilicum Linn) Powder - Haris Nurdin Pratama; Ratih Dewi Dwiyanti; Ahmad Muhlisin (Tropical Health and Medical Research, 2020)
Malassezia furfur is very easy to infect the skin of people who are often in damp places with higher water content for a long time. One of the plants that can add to inhibit the growth of Malassezia furfur is basil. The purpose of this study was to determine the number of Malassezia furfur mushroom growths formed on the SDA media with the addition of basil powder concentrations of 2%, 4%, 6%, and 8% on day 5. The method used in this study was experimental with a post-test research design with control. The material used is the leaves of basil plants obtained from basil plantations in Sukamara Village, Landasan Ulin Banjarbaru, Indonesia. The results of the study, Malassezia furfur, grew in all concentrations with a creamy colony, smooth and soft texture with sizes between 1-2 mm and microscopically obtained hyphae and spores. The conclusion of this study, Malassezia furfur mushroom growth in all concentrations of 2%, 4%, 6%, and 8% with the results of the number of colonies in a row that is 798 colonies, 755 colonies, 661 colonies, 622 colonies. The results showed a decrease in the name of colonies, with each increase in concentration.